Spell Bound : A Hex Hall Novel - Hawkins, Rachel (London Simon & Schuster, 2012)
Ever since she started at Hectate "Hex" Hall a school for "gifted" students Sophie Mercer's life has been a whirlwind of disasters. But now Sophie is facing her biggest crisis so far, and this time it's her life, and the lives of everyone she loves that are at stake"--Publisher.
Keywords: Magic -- Demonology -- Paranormal fiction